Polyvalent human immunoglobulin for infectious diseases: Potential to circumvent antimicrobial resistance - Pedraza-Sánchez, Sigifredo; Cruz-González, Adrián; Palmeros-Rojas, Oscar; Gálvez-Romero, José Luis; Bellanti, Joseph A.; Torres, Martha (Frontiers in Immunology, 2023)
Antimicrobial resistance (AMR) is a global health problem that causes more than 1.27 million deaths annually; therefore, it is urgent to focus efforts on solving or reducing this problem. The major causes of AMR are the misuse of antibiotics and antimicrobials in agriculture, veterinary medicine, and human medicine, which favors the selection of drug-resistant microbes. One of the strategies proposed to overcome the problem of AMR is to use polyvalent human immunoglobulin or IVIG. The main advantage of this classic form of passive immunization is its capacity to enhance natural immunity mechanisms to eliminate bacteria, viruses, or fungi safely and physiologically. Experimental data suggest that local administration of IVIG for some infections may produce better results with a lower dose than intravenous application. This review presents evidence supporting the use of polyvalent human immunoglobulin in AMR and the potential and challenges associated with its proposed usage.